2013
DOI: 10.1073/pnas.1311232110
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of Munc18c and Munc18-1 reveal conserved and divergent mechanisms of Sec1/Munc18 proteins

Abstract: Sec1/Munc18 (SM) family proteins are essential for every vesicle fusion pathway. The best-characterized SM protein is the synaptic factor Munc18-1, but it remains unclear whether its functions represent conserved mechanisms of SM proteins or specialized activities in neurotransmitter release. To address this question, we dissected Munc18c, a functionally distinct SM protein involved in nonsynaptic exocytic pathways. We discovered that Munc18c binds to the trans-SNARE (soluble N-ethylmaleimide-sensitive factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
154
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(159 citation statements)
references
References 83 publications
5
154
0
Order By: Relevance
“…Furthermore, proteoliposomes reconstituted with SNAREs only support lipid mixing, demonstrating that SNAREs alone can drive membrane fusion (8, 19 -24). Similarly, it was shown that Munc18-1 accelerates SNARE-mediated proteoliposome fusion, supporting the notion that Munc18-1 is part of the minimal fusion machine (12,25).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, proteoliposomes reconstituted with SNAREs only support lipid mixing, demonstrating that SNAREs alone can drive membrane fusion (8, 19 -24). Similarly, it was shown that Munc18-1 accelerates SNARE-mediated proteoliposome fusion, supporting the notion that Munc18-1 is part of the minimal fusion machine (12,25).…”
supporting
confidence: 58%
“…The severity of the knock-out phenotype could be explained equally well by the losing of inhibitory capping on syntaxin-1a. Second, Munc18-1 has the capacity of accelerating SNARE-dependent proteoliposome fusion significantly (12,25). However, the caveat here is that Syt1 is not included in those experiments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Supporting the hypothesis of the importance of the Sx C-terminus, Yu et al (2013) showed that Munc18c positively influenced SNARE-complex formation using a liposomal fusion assay similar to that used by Brandie et al (2008). In these later experiments, the t-SNARE complex consisted of untagged Sx4-TMD and N-terminally His tagged SNAP23 (Yu et al, 2013) and thrombin was not used.…”
Section: The Effect Of the Sx C-terminusmentioning
confidence: 83%
“…In these later experiments, the t-SNARE complex consisted of untagged Sx4-TMD and N-terminally His tagged SNAP23 (Yu et al, 2013) and thrombin was not used.…”
Section: The Effect Of the Sx C-terminusmentioning
confidence: 99%